(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The present paper unveils vulnerabilities that remain among the low-income community in the megacity of Dhaka, while millions of people live in fragile housing conditions and depend on various informal economic activities. Based on extensive review of covid-19 related data collected from relevant institutions (e.g. IECDR), focus group discussions and case studies of the low income people living in three selected slums and some low income areas in Dhaka City, the present study explores that low income people have extremely been suffering from covid-19 pandemic induced lock-down. In addition to Covid-19 infections, the major concern of this group of people lies in the loss of income. As a result, most of them suffered tremendously from starvation and deprivation of some basic needs. Study findings also show that a significant part of this community left the capital city not being able to maintain them. In order to ensure the existence of this significant people with their support to the society, a special scheme of incentives should be provided while enhancing their resilience to the pandemic like covid-19. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 9-20